Validity, reliability, and feasibility of physical literacy assessments designed for school children: a systematic review - Barnett, L. M.; Jerebine, A.; Keegan, R.; Watson-Mackie, K.; Arundell, L.; Ridgers, N. D.; Salmon, J.; Dudley, D. (Sports Medicine, 2023)
Background: While the burgeoning researcher and practitioner interest in physical literacy has stimulated new assessment approaches, the optimal tool for assessment among school-aged children remains unclear. Objective: The purpose of this review was to: (i) identify assessment instruments designed to measure physical literacy in school-aged children; (ii) map instruments to a holistic construct of physical literacy (as specified by the Australian Physical Literacy Framework); (iii) document the validity and reliability for these instruments; and (iv) assess the feasibility of these instruments for use in school environments. Design: This systematic review (registered with PROSPERO on 21 August, 2022) was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement. Data Sources: Reviews of physical literacy assessments in the past 5 years (2017 +) were initially used to identify relevant assessments. Following that, a search (20 July, 2022) in six databases (CINAHL, ERIC, GlobalHealth, MEDLINE, PsycINFO, SPORTDiscus) was conducted for assessments that were missed/or published since publication of the reviews. Each step of screening involved evaluation from two authors, with any issues resolved through discussion with a third author. Nine instruments were identified from eight reviews. The database search identified 375 potential papers of which 67 full text papers were screened, resulting in 39 papers relevant to a physical literacy assessment. Inclusion and Exclusion Criteria: Instruments were classified against the Australian Physical Literacy Framework and needed to have assessed at least three of the Australian Physical Literacy Framework domains (i.e., psychological, social, cognitive, and/or physical). Analyses: Instruments were assessed for five aspects of validity (test content, response processes, internal structure, relations with other variables, and the consequences of testing). Feasibility in schools was documented according to time, space, equipment, training, and qualifications. Results: Assessments with more validity/reliability evidence, according to age, were as follows: for children, the Physical Literacy in Children Questionnaire (PL-C Quest) and Passport for Life (PFL). For older children and adolescents, the Canadian Assessment for Physical Literacy (CAPL version 2). For adolescents, the Adolescent Physical Literacy Questionnaire (APLQ) and Portuguese Physical Literacy Assessment Questionnaire (PPLA-Q). Survey-based instruments were appraised to be the most feasible to administer in schools. Conclusions: This review identified optimal physical literacy assessments for children and adolescents based on current validity and reliability data. Instrument validity for specific populations was a clear gap, particularly for children with disability. While survey-based instruments were deemed the most feasible for use in schools, a comprehensive assessment may arguably require objective measures for elements in the physical domain. If a physical literacy assessment in schools is to be performed by teachers, this may require linking physical literacy to the curriculum and developing teachers` skills to develop and assess children`s physical literacy.